2013
DOI: 10.1007/s00267-013-0139-0
|View full text |Cite
|
Sign up to set email alerts
|

Local Farmers’ Perceptions of Climate Change and Local Adaptive Strategies: A Case Study from the Middle Yarlung Zangbo River Valley, Tibet, China

Abstract: Climate change affects the productivity of agricultural ecosystems. Farmers cope with climate change based on their perceptions of changing climate patterns. Using a case study from the Middle Yarlung Zangbo River Valley, we present a new research framework that uses questionnaire and interview methods to compare local farmers' perceptions of climate change with the adaptive farming strategies they adopt. Most farmers in the valley believed that temperatures had increased in the last 30 years but did not note … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
52
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 21 publications
3
52
0
4
Order By: Relevance
“…These evidences clearly show that the high-altitude and other low-lying regions of Nepal have experienced climatic variability. Similar changes of climatic pattern on temperature, rainfall and snowfall have also been perceived by the people living in other neighboring high-altitude regions of South Asia, such as eastern Himalaya (Sharma et al 2009); Bhutan (RSPN 2012); Bangladesh (Huda 2013); Himachal state of India (Basannagari and Kala 2013;Kaul & Thornton 2014); Uttaranchal state of India (Kumar et al 2008); northeast Sikkim Himalaya (Mishra et al 2014); northern highland of Pakistan (Joshi et al 2013;Gioli et al 2014;Maryam et al 2014); also in northwest Yunnan region (Haynes & Yang 2013) and Tibet region (Li et al 2013) of China. Bickerstaff (2004) defined perception as subjective evaluation that evolves from experiences and personality disposition that affects one's individual behavior and attitude while Wakefield et al (2001) narrated that individual's everyday experience and exposure to media and other outside sources helps in forming and reinforcing perception.…”
Section: Introductionmentioning
confidence: 93%
“…These evidences clearly show that the high-altitude and other low-lying regions of Nepal have experienced climatic variability. Similar changes of climatic pattern on temperature, rainfall and snowfall have also been perceived by the people living in other neighboring high-altitude regions of South Asia, such as eastern Himalaya (Sharma et al 2009); Bhutan (RSPN 2012); Bangladesh (Huda 2013); Himachal state of India (Basannagari and Kala 2013;Kaul & Thornton 2014); Uttaranchal state of India (Kumar et al 2008); northeast Sikkim Himalaya (Mishra et al 2014); northern highland of Pakistan (Joshi et al 2013;Gioli et al 2014;Maryam et al 2014); also in northwest Yunnan region (Haynes & Yang 2013) and Tibet region (Li et al 2013) of China. Bickerstaff (2004) defined perception as subjective evaluation that evolves from experiences and personality disposition that affects one's individual behavior and attitude while Wakefield et al (2001) narrated that individual's everyday experience and exposure to media and other outside sources helps in forming and reinforcing perception.…”
Section: Introductionmentioning
confidence: 93%
“…Studies across multiple developing countries suggest variability among farmers’ perceptions of how climate is changing . In early work, Diggs found that farmers living in drought‐prone areas are more likely to describe climate as becoming drier and warmer than are farmers living in relatively wetter areas .…”
Section: Introductionmentioning
confidence: 99%
“…Studies across multiple developing countries suggest variability among farmers' perceptions of how climate is changing. (1)(2)(3)(4)(5)(6) In early work, Diggs found that farmers living in drought-prone areas are more likely to describe climate as becoming drier and warmer than are farmers living in relatively wetter areas. (7) Although this work did not compare perceptions to the historical record, it is perhaps not surprising that individuals in differing agroecological zones would experience, and therefore report, climate differently.…”
Section: Overall Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies (Apata, Samuel, & Adeola, 2009;Li et al, 2013;Vedwan & Rhoades, 2001;Wii, & Ziervogel, 2012) have shown that farmer's perceptions of climate variability and change are in sync with climate trends in their regions. Accurate perceptions of climate variability and change can help farmers to take effective measures to protect their livelihoods against threats from local environmental change; conversely, understanding how farmers perceive threats from climate change (or not) can help policymakers anticipate the diversity of strategies and behaviors that will ultimately shape the vulnerability of agriculture in the coming decades.…”
mentioning
confidence: 98%